Preliminary characterization in antimicrobial stability, phytochemical and toxicity profiling of Sauropus androgynus L. (sweet leaf vegetable) extract: Evaluate the potential of new antimicrobial agent - Wong, Jun Xian; Rukayadi, Yaya; Zainal Abedin, Nur Hanani; Abdul Mutalib, Noor Azira; Ramli, Suzita; Kuan, Chee Hao (Elsevier Ltd, 2025)
Chemical preservatives are well-recognized in food preservation, however, overuse may cause adverse effects on consumer health. Therefore, researchers prompted their contribution to develop plant-based preservatives, which have become promising alternative candidates. This research sought to characterize the antimicrobial activity, toxicity and phytochemical analyses of ethanolic extract of Sauropus androgynus (EESA). The tested strains were mainly foodborne pathogens and spoilage microbes, inhibited in agar well diffusion (7.00–9.33 mm of inhibition zones). Minimum inhibition concentration (MIC; 1.56–50.00 mg/mL), minimum bactericidal concentration (MBC; 1.56–50.00 mg/mL) and minimum fungicidal concentration (MFC; 3.13–50.00 mg/mL) were recorded as well. Time-kill analysis showed microorganisms were killed completely at 2-4 × MIC except Bacillus cereus and Candida parapsilosis but below the required infectious doses (<5.00 log CFU). The sporicidal effect of EESA against spores of B. cereus and B. subtilis were reduced until 2.36–3.12 log spores/mL. EESA was achieved the inhibition of conidial germination of Aspergillus flavus (96%) and Rhizopus oryzae (100%). The antimicrobial activity was mostly unaffected at various temperatures and pHs, except extreme temperatures (80 and 100 °C). Nine major components detected in gas chromatography-mass spectrometry and might correlate to the antimicrobial activity of EESA. Toxicity analysis of EESA was investigated using brine shrimp assay a low mortality rate (LC50 552.8 mg/mL) was revealed and indicated safe for human consumption, according to Meyer's Index (LC50; >1 mg/mL). In conclusion, EESA (100 mg/mL) potentially inhibited all tested microbes provided without compromising its stability. EESA can potentially to be directed and incorporated into the confirmation of future food applications.